SISTEM PAKAR FUZZY UNTUK MANAJEMEN DAUR HIDUP PRODUK - Tamaela, Gysber J. (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2007)
Every product has its certain life cycle, whether, for example, it preserve in the market or have to be withdrawed from the market. Some criterias are important to determine those decisions. But they are not in numerical form but categorial one. Fuzzy logic is a tool to transform those categorial form to numerics using membership function. This research was trying to helps management as an expert system to make a decision based on computer software.